Gingival crevicular blood: A noninvasive pathway to determine blood glucose level in periodontal patients - Sohini Banerjee; Rajashree Ganguly; Tamal Kanti Pal (Indian Journal of Dental Sciences, 2017)
Aim: The aim of this study is to determine the efficacy and reliability of estimation of blood glucose level of patients with diabetes suffering from periodontal disease using gingival crevicular blood through periodontal pockets. Materials and Methods: A total of 70 patients with a known history of diabetes mellitus suffering from chronic periodontal diseases having visible signs of gingival inflammation were selected for the study based on other inclusion criteria. The excess gingival crevicular blood produced during routine periodontal examinations were carefully collected onto the glucometer test strips, and blood glucose levels were estimated with the help of glucose self-monitoring device (Glucometer). The finger-prick blood samples were also collected and glucose levels were also estimated using Glucometer. Patient's venous blood samples were collected at the same time, and blood glucose estimations were done using conventional laboratory measurements. Results: The results of this study revealed a strong correlation between (a) the gingival crevicular blood glucose (GCBG) and finger-prick blood glucose (Pearson's correlation r = 0.982; P < 0.001); and also (b) between GCBG and corrected venous blood glucose (Pearson's correlation r = 0.891; P < 0.001). Conclusion: Oozing blood from the gingival crevice during the routine periodontal examination can be used as a quick, noninvasive, chair-side diagnostic mode to estimate, and/or monitor blood glucose levels in periodontal patient suffering from diabetes mellitus with the help of Glucometer.